Rancang bangun detektor ketinggian air di landasan pacu pesawat terbang berbasis internet of things (Water level detector fabrication design on an airplane runway based on the internet of things) - Puti Aulia Mardiah; - Yohandri (PILLAR OF PHYSICS, 2019)
The runway of an aircraft is designed to keep it dry even if it rains to avoid hydroplaning. Hydroplaning is a plane slip on the runway due to standing water. In accordance with regulations from the Airport Directorate, DGCA NO. KP 212 in 2017, the operational requirement for runways to be able to serve landings and aircraft flights is when there is a maximum of 3 mm of standing water on the runway surface. The design of the water level detector on the runway uses the Arduino Mega 2560 as a microcontroller which processes and sends the detected data to the thingspeak via the internet network. Performance specifications for water level detectors are water level sensor designs, U detector pipes, runways, electronic circuits. The water level sensor is a touch sensor that is designed and printed on a PCB board with horizontal and vertical strip designs. However, the level of accuracy and accuracy of the vertical sensor strip design is higher than the horizontal sensor strip design. Detected data will be processed in Arduino Mega 2560 and typed into the thingspeak page using the internet network. Data output can be accessed via a PC or smartphone connected to the internet network. The results of comparison with standard tools found the average percentage of errors for the horizontal sensor strip design was 97.08% while for the vertical sensor strip design was 4.98%. From the comparison results, the average percentage of accuracy for the horizontal sensor strip design is 8.57% and for the vertical sensor strip design is 95.01% with precision of 42.32% and 84.77%.Keywords : Arduino Mega 2560, Internet Of Things, thingspeak, sensor strip design